The Potential of Limestone as Preserving Agent for Bamboo Fibre - Nur Adilah Fitri; Nasrul Fikry Che Pa (Progress in Engineering Application and Technology, 2022)
Bamboo fibres have recently attracted a lot of attention as a viable substitute for synthetic fibres for composite building applications, due to the rising awareness of ecologically friendly biomaterials. Alkaline treatment is commonly known to chemical treatment procedure for modifying the texture of natural fibres. NaOH is a commonly used alkaline that is used to treat bamboo fibre.  However, it is extremely caustic and can cause tissue damage if it comes into contact with skin. This research is to investigate the effectiveness of the limestone which is not a synthetic chemical to treat the bamboo fibre. The tensile strength of bamboo fibre is obtained via universal tensile machine (UTM). The morphological structure of untreated/controlled and treated bamboo fibre investigated using scanning electron microscope (SEM). Finally, research come into the functional group of the bamboo fibres using Fourier-transform infrared spectroscopy (FTIR). The bamboo fibre that had been soaked in 4 wt.% CaCO3 for 4 hours exhibited the highest tensile strength. It is because the decreased of lignin makes the bamboo fibre more durable. CaCO3 has been shown to be effective in the preservation of bamboo fibres.